Strongheart : wonder dog of the silver screen - Fleming, Candace; Rohmann, Eric (New York : Schwartz & Wade Books, 2018)
A German shepherd is transformed from Etzel, a police dog in Berlin, to Strongheart, a silent movie star that will need his best acting skills to prove himself innocent of attacking a girl.
Includes bibliographical references (pages 242-245).
Keywords: German shepherd dog -- Juvenile fiction; German shepherd dog -- Fiction; Dogs -- Fiction; Working dogs -- Fiction; Motion pictures -- Production and direction -- Fiction; JUVENILE FICTION -- Action & Adventure -- Survival Stories; JUVENILE FICTION -- Animals -- Dogs; JUVENILE FICTION -- Historical -- United States -- 20th Century; German shepherd dog -- Juvenile fiction; German shepherd dog -- Fiction; Working dogs -- Fiction; Dogs -- Fiction; Fiction; Juvenile works; Novels; Novels